2000
DOI: 10.1016/s0248-4900(00)01079-0
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome‐centriole abnormalities are markers for abnormal cell divisions and cancer in the transgenic adenocarcinoma mouse prostate (TRAMP) model

Abstract: We utilized the transgenic adenocarcinoma mouse prostate (TRAMP) model to study the formation of abnormal mitosis in malignant tumors of the prostate. The results presented here are focused on centrosome and centriole abnormalities and the implications for abnormal cell divisions, genomic instability, and apoptosis. Centrosomes are microtubule organizing organelles which assemble bipolar spindles in normal cells but can organize mono-, tri-, and multipolar mitoses in tumor cells, as shown here with histology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…It has been argued that centriole engagement not only prevents centrosome re-duplication, but also contributes to the integrity of the centrosome which is important for bipolar chromosome segregation. Mis-regulation of the centrosome cycle significantly impacts human health and is closely associated with tumorigenesis, [12][13][14] developmental problems 15 and aging. 16 Recent work demonstrated that the cohesin complex localizes to centrosomes and spindle poles.…”
Section: Centrosomesmentioning
confidence: 99%
“…It has been argued that centriole engagement not only prevents centrosome re-duplication, but also contributes to the integrity of the centrosome which is important for bipolar chromosome segregation. Mis-regulation of the centrosome cycle significantly impacts human health and is closely associated with tumorigenesis, [12][13][14] developmental problems 15 and aging. 16 Recent work demonstrated that the cohesin complex localizes to centrosomes and spindle poles.…”
Section: Centrosomesmentioning
confidence: 99%
“…Electron microscope images revealed supernumerary centrioles in centrosomes of humans and animal model tumors, including leiomyosarcoma, neuroblastoma, glioma and thymic carcinoid tumors (Friedlander, 1982;Kaneko et al, 1980;Seifert, 1978;Sharp et al, 1981Sharp et al, , 1982Ring, 1982). Subsequent systematic analyses of centrosomes in human breast carcinomas and a mouse model for prostate cancer revealed a range of abnormalities in centrosome structure including: excess number of centrioles, increased pericentriolar material, abnormal centriole orientation, and inverted polarity of centrosome location (i.e., with the centrosome located within the cell in a basal rather than an apical position relative to the nucleus) Schatten et al, 2000). These structural centrosome abnormalities have been implicated as a potential cause of loss of cell and tissue architecture seen in cancer (i.e.…”
Section: Centrosome Amplification In Cancermentioning
confidence: 99%
“…Centrosome amplification and chromosomal instability can be induced by over-expression of the centrosomal protein pericentrin and by over-expression of the centrosome kinase BTAK/STK15, suggesting that alternative mechanisms may lead to centrosome defects and consequent genomic instability (Pihan et al, 2001;Zhou et al, 1998). In prostate cancer, centrosome amplification has been implicated in the development of abnormal mitoses and CIN facilitating progression to advanced stages of the disease (Ouyang et al, 2001;Pihan et al, 2001;Schatten et al, 2000). Strong support for a direct mechanistic link between centrosome amplification and CIN is suggested by the significant linear correlation between centrosome amplification and the rate of change in karyotype (CIN) seen in human breast tumors .…”
Section: Correlation Of Centrosome Amplification Aneuploidy and Chromentioning
confidence: 99%
“…The term 'centrosome amplification' is commonly used to describe centrosomes that appear significantly larger than normal (as defined by staining of structural centrosome components, such as g-tubulin, which exceeds that seen in the corresponding normal tissue or cell type), centrosomes that contain an abnormal number of centrioles, or the presence of more than two centrosomes in a single cell (Lingle and Salisbury, 1999;Schatten et al, 2000). Numerous studies have also implicated centrosome amplification as a potential origin of chromosomal instability in the development of a variety of human tumors (Pihan et al, 1998;Ghadimi et al, 2000;Pihan et al, 2001;Sato et al, 2001;Lingle et al, 2002;Weaver et al, 2002;Al-Romaih et al, 2003;Mayer et al, 2003;Pihan et al, 2003;Bennett et al, 2004).…”
Section: Introductionmentioning
confidence: 99%